THIES, A DYNAMIC URBAN SPACE: PUBLIC SANITATION AND POPULAR PRACTICES - (:unkn) unknown (My University, 2017)
In Africa, as elsewhere, an urban dynamic space always faces some problems on fundamental needs satisfaction for its populations (live, work, circulate, become enlightened the body and the sprit). In a briefer way, the management of the public sanitation remains long-lived in african cities. The study on household waste was used as an excuse to approach this reality, through a multidisciplinary approach including several levels of analysis (geography, sociology, health, etc.). In fact, situated in the zone of natural spatial expansion of the Senegalese capital and being also an essential element of the triangle Dakar-Thies-Mbour, the urban area of Thies undergoes a steady spatial spreading, marked by deep transformations, in a context of absence of sustainable policy of the care of its environment. From several tools (diachronic mapping, field surveys, conversations, photos…) intended to make a MRI of the city, this theory handles straightaway the history of the formation of Thies city and studies its demographic and economic dynamism. Then it uncorks in a diachronic analysis of the land use and the organizational and structural aspects of the sector of waste. It deals with the dynamics of CBOs and their contribution in the fight against the degradation of urban spaces of the environment. And finally, it presents the outlook of the management of sanitation problems in African urban areas. This thesis highlights some public sanitation problems, behavioral emergencies and malfunctions that increase as the city spreads out and that management systems are struggling to master them.
Keywords: African Research